The assessment of substances preferred by the cases, who applied to the adolescent addiction center, based on the [year]s - Yüncü, Z.; Bayram, A. T.; Altıntoprak, E.; Akgür, S. A.; Coşkunol, H.; Aydın, C.; Tamar, M. (Journal of Dependence, 2008)
Objective: Alcohol and substance use disorder (AUD) affects a significant segment of society. The first substance tried by individuals with AUD and the age at which they tried this substance vary from year to year. This study aimed to determine changes in some clinical characteristics (age of use, type of substance used, gender) among cases presenting to an addiction center where children and adolescents receive treatment. Method: The file records of cases presenting to an adolescent addiction center between September 2003 and September 2005 (dI) and September 2005 and September 2007 (dII) were scanned. The obtained information was analyzed using SPSS 11. Statistical significance was accepted as p<0.05. Findings: 646 cases applied during this period. 49.5% (n: 320) of the applicants were in dI, and 50.5% (n: 326) were in dII. The arithmetic mean age of the cases was found to be 16.25±1.798 for dI and 16.48±1.678 for dII (p:0.053). When we evaluated according to gender, it was determined that the rate of female patients was 10.3% in dI, 18.1% in dII, the rate of male patients was 89.7% in dI and 81.9% in dII (p:0.007). It was found that cases applying to dI had used 74.7% cannabis, 56.6% ecstasy, 49.7% inhalants, 42.3% alcohol, 31% benzo, 2.7% cocaine, and 0.3% heroin while those applying to dII had used 77.7% cannabis, 66.5% ecstasy, 44.9% alcohol, 36.6% inhalants, 27.5% benzo, and 2.4% cocaine. A decrease in inhalant use was also observed, while an increase in ecstasy use was observed. Discussion: The age at first attempt at substance use reported in this study is consistent with the literature. The substances used and gender distribution of adolescent substance users vary from year to year. While cigarettes are still the first substance tried, there has been a significant increase in cannabis and ecstasy use.